Failure Analysis of First-Stage Vane in a GT13E1 Gas Turbine at Combined Cycle Power Plant - Mochammad Nafi Khumasia; Fahmi Mubaroka (Riviera Publishing, 2026)
The first-stage vane of a GT13E1 gas turbine plays a critical role in directing high-temperature combustion gases toward the rotor blades and therefore operates under severe thermal conditions. During a field inspection at a combined-cycle power plant, significant damage was identified in the vane platform endwall region, including coating degradation, oxidation, and material loss, which resulted in hole formation. The damage was concentrated at the platform endwall corner. This study investigated the damage characteristics and failure mechanism through visual inspection, hardness testing, X-ray fluorescence (XRF) analysis, scanning electron microscopy (SEM), and metallographic examination. The results indicated localized overheating at the platform endwall corner. The silo comb geometry likely promoted secondary flow development and local turbulence, resulting in a non-uniform temperature distribution and the formation of hot spots near the endwall region. Elevated temperatures accelerated thermally grown oxide (TGO) layer formation at the coating interface, leading to thermal barrier coating (TBC) spallation. Subsequent exposure of the nickel-based alloy substrate promoted oxidation, erosion, microstructural degradation, and thermal fatigue crack initiation. Progressive crack propagation eventually caused structural damage to the vane platform. The findings indicate that localized thermal distress associated with secondary flow effects was the dominant failure mechanism and provide insights for inspection planning, cooling system design evaluation, and life management strategies for industrial gas turbine vanes.